Engineering mechanics : dynamics - Bedford, Anthony; Fowler, Wallace (Reading, MA. : Addison-Wesley, 1996)
Introduction; Motion of a point; Force, mass and acceleration; Energy methods; Momentum methods; Planar kinematics of rigid bodies; Two-dimensional dynamics of rigid bodies; Energy and momentum in planar rigid-body dynamics; Three-dimensional kinematics and dynamics of rigid bodies; Vibrations.
Includes index.
Keywords: Mechanics; Mechanics